Legal Regulation of Entrepreneurship under Import Substitution in the Russian Federation - P. Albov, Aleksey P. Albov; V. Krasnenkova, Elena; O. Teplova, Daria; Yu. Yakubenko, Konstantin; V. Nikolyukin, Stanislav (Opción, 2019)
The article is intended to justify the need for implementation of an effective model of legal base development for small business and entrepreneurship, as well as minimization of negative processes from the sectional policy. The leading research method for this problem is the comparative and legal analysis of legal framework using mathematical models for research of entrepreneurship in Russia that can give scientific credence to the conclu- sion of advantages and disadvantages of legal regulation of entrepreneurship and identify degenerative processes in the structure of the relationship between government and business. The main results show that lack of real effective legal mechanisms that ensure effective activity of enterprises, hyper administration, corruption, regional deformations of juridical policy – all these factors represent an obvious obstacle to entrepreneurship development and mitigation of negati- ve consequences in the economy under sanctions. Materials of the article may be useful for planning of juridical policy and prospective cooperation in the international legal aspect that enable imple- mentation of joint projects, for analysis of international investment policy prospects in respect of Russian economy, as well as for analysis of the main social and political trends under sanctions.